A Simple Application of Lightweight Fusion to Proving the Equivalence of Abstract Machines - Danvy, Olivier; Millikin, Kevin (BRICS Report Series, 2007)
We show how Ohori and Sasano's recent lightweight fusion by fixed-point promotion provides a simple way to prove the equivalence of the two standard styles of specification of abstract machines: (1) as a transition function together with a `driver loop' implementing the iteration of this transition function; and (2) as a function directly iterating upon a configuration until reaching a final state, if ever. The equivalence hinges on the fact that the latter style of specification is a fused version of the former one. The need for such a simple proof is motivated by our recent work on syntactic correspondences between reduction semantics and abstract machines, using refocusing.